Determination of urban regeneration project conflict causes for the Turkish construction industry - Demirdogen, Gokhan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2023)
Urban regeneration projects come into prominence for various reasons such as the economic development of cities, earthquakes, urban decay, and lack of land for expansion. Due to the complexity of urban regeneration projects and the participation of multiple stakeholders, conflicts, which impede the successful implementation of projects, among stakeholders are unavoidable. There is limited knowledge about urban regeneration conflict causes in the literature. Existing studies have employed case study methodology and determined projectspecific conflict causes. According to the literature review analysis, there has not been a single study to establish the priority orders of urban regeneration conflict causes based on risk severity, risk occurrences, and risk impact in urban regeneration projects. Therefore, this study aimed to identify and determine the urban regeneration conflict causes specific to Turkiye. In the article, the authors detected 69 urban regeneration conflict causes after a focus group discussion. The identified conflict causes were analyzed with the fuzzy TOPSIS methodology by considering the conflict causes' impacts on project cost overruns, delays in the project schedule, and project quality. The analysis showed that Construction abandonment by a construction company and Bankruptcy of a construction company are the most significant conflict causes for urban regeneration projects, respectively. The Imperfect platform for appeal expression and public participation conflict cause was found to be the least important conflict specific to Turkiye. Practitioners can use the study results to develop urban regeneration strategies and policy formulation, prevent conflicts, or mitigate tension among stakeholders.
Keywords: Conflict management; construction management; urban regeneration; RISK-ASSESSMENT; FUZZY TOPSIS; STAKEHOLDERS; PERCEPTION; Architecture